2021
DOI: 10.3390/app112210697
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Spike Protein of SARS-CoV-2 and Human Virus Receptor ACE2 Using Two-Color Fluorescence Cross-Correlation Spectroscopy

Abstract: Infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the cause of coronavirus disease 2019 (COVID-19), is initiated by the interaction between a receptor protein, angiotensin-converting enzyme type 2 (ACE2) on the cell surface, and the viral spike (S) protein. This interaction is similar to the mechanism in SARS-CoV, a close relative of SARS-CoV-2, which was identified in 2003. Drugs and antibodies that inhibit the interaction between ACE2 and S proteins could be key therapeutic methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The amount of sample required for the analysis was extremely low, due to the exploitation of the miniaturized F4 variant, and the analysis time being below 30 min for each analysis. In agreement with pre-existing "single component" studies [29][30][31][32], we observed that serum's heme-scavenging power is mainly represented by SA and Hx, and to a much lower degree by some immunoglobulins. IgG scavenging contributions in the presence of clinically relevant free heme levels (5-40 µM) can instead be considered negligible.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…The amount of sample required for the analysis was extremely low, due to the exploitation of the miniaturized F4 variant, and the analysis time being below 30 min for each analysis. In agreement with pre-existing "single component" studies [29][30][31][32], we observed that serum's heme-scavenging power is mainly represented by SA and Hx, and to a much lower degree by some immunoglobulins. IgG scavenging contributions in the presence of clinically relevant free heme levels (5-40 µM) can instead be considered negligible.…”
Section: Introductionsupporting
confidence: 91%
“…In the case of serum-heme interactions, it is to be noted that the experimental difficulties are numerous, and the matrix is very complex. Consequently, all the experiments conducted up to date aimed at understanding the involvement of serum protein for heme scavenging were carried out in an isolated and compartmentalized way, which on one hand facilitates recognition, but on the other hand represent only a partial result that does not necessary fully translate to the real matrix or the physiological state [29][30][31][32]. To examine heme-protein interactions in a more representative scenario, where proteins are simultaneously present in the matrix (in their biological concentrations) and can both concur and compete for binding, it is necessary to develop a detection system that simplifies the sample while preserving its native state.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, molecular dynamics simulations proved helpful in the prediction of new spike variants’ behaviors and the effectiveness of human neutralizing antibodies [ 24 ]. Furthermore, to develop a high-throughput platform to screen neutralizing antibodies against SARS-CoV-2, Fujimoto et al carried out two-color fluorescence cross-correlation spectroscopy experiments (FCCS), investigating the quantitative interactions between the spike protein and human soluble ACE2 receptor [ 25 ]. Conversely, Rusanen and co-workers labeled the viral spike and nucleoprotein antigens and incubated them with serum samples, developing a “mix and read” immunoassay based on Förster resonance energy transfer (FRET) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant proteins were expressed in murine neuroblastoma Neuro2a cells (CCL-131, ATCC, Manassas, VA, USA) and purified as previously reported [18].…”
Section: Protein Purificationmentioning
confidence: 99%
“…FCCS measurements were performed using a ConfoCor 3 system combined with an LSM 510 META (Carl Zeiss, Jena, Germany) through a C-Apochromat 40×/1.2 NA Korr UV-VIS-IR water immersion objective (Carl Zeiss) as reported previously [18]. Briefly, the relative cross-correlation amplitude (RCA) was calculated as the following equation.…”
Section: Fluorescence Cross-correlation Spectroscopy (Fccs)mentioning
confidence: 99%